Osmosis, hybridisation, symbiosis – From biophilia to interspecies regenerative design - Chiara Rizzi (Agathón, 2025)
This paper offers a reflection on a broader field of investigation developed through the activities of the NatureCity LAB at the University of Basilicata. The aim of exploring three operative categories is to focus on three processes through which the relationship between Architecture and Nature can generate spatial conditions for welcoming new alliances between humans and non-humans. Osmosis, hybridisation, and symbiosis are thus the key processes through which the regenerative potential of architecture, the city, and the landscape are investigated to ensure the well-being of the individuals who inhabit them. The research draws on a hypothesis, biophilia, a point of observation, the City of Matera, and case studies to trace a research trajectory around the Nature-City paradigm to outline a design perspective: interspecies regenerative architecture.